The Predictive Value of Tumor Mutation Burden on Clinical Efficacy of Immune Checkpoint Inhibitors in Melanoma: A Systematic Review and Meta-Analysis - Ning, Biao; Liu, Yixin; Wang, Miao; Li, Yi; Xu, Tianzi; Wei, Yongchang (Frontiers in Pharmacology, 2022)
Background: Tumor mutational burden (TMB) is a genomic biomarker that can predict favorable responses to immune checkpoint inhibitors (ICI). Although we have better understanding of TMB in cancer immunity and cancer immunotherapy, the relationship between TMB and the clinical efficacy of ICI remains unknown in the treatment of melanoma patients. Here, we conduct a systematic review and meta-analysis to evaluate the predictive value of TMB on the efficacy of ICI in patients with melanoma. Methods: We systematically collected the data from PubMed, Embase, Cochrane Library, CNKI, China Biomedical Database (CBM) and Wanfang Database. The end date was set up to June 26, 2021. We included retrospective studies or clinical trials of ICI that reported hazard ratios (HR) for overall survival (OS) and/or progression-free survival (PFS) according to TMB. Data for 1493 patients from 15 studies were included. In addition, pooled effect size, heterogeneity analysis, sensitivity analysis, publication bias detection, and subgroup analysis were performed based on the included data. Results: Patients with high TMB showed significantly improved OS (HR=0.49, 95%CI: 0.33, 0.73; P=0.001) and PFS (HR=0.47, 95%CI: 0.33, 0.68; P<0.001) compared with patients with low TMB. The subgroup analysis results showed that heterogeneity was substantial in the targeted next-generation sequencing (NGS) group. Publication bias was detected, and the results were visualized using the funnel chart. And sensitivity analysis and Trim and Fill Method analysis showed that our results were stable and reliable. Conclusion: High TMB is associated with improved of OS and PFS in melanoma patients treated by ICI. TMB determined with NGS should be standardized to eliminate heterogeneity. Therefore, the role of TMB in identifying melanoma patients who may benefit from ICI should be further determined in more randomized controlled trials in the future.